1979
DOI: 10.1111/j.1432-1033.1979.tb12966.x
|View full text |Cite
|
Sign up to set email alerts
|

Formate‐Nitrite Reduction in Escherichia coli K12

Abstract: (Kccei\ctl hij\i.n1hi.r 7. l S 7 S .I~IIIU~II~~ IS. lV7cJ) Some physiological characteristics of the formate nitrite reductase activity were studied on whole cells.1. Highest level of activity was found in cells grown in anaerobiosis on glycerol in the presence of nitrite. Maximal activity was obtained at pH 8 and at 45°C. Copper ions and cyanide inhibit the activity whereas 0.1 mM azide is without effect.2. No reduction of nitrite was detected in the presence of oxygen, even at very low concentrations. Nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…We found that the inhibition profile of the nitrite reductase activity of the purified cytochrome c552 with several inhibitors coincided with that of the cellular formate/ nitrite reductase [33]. Cytochrome c552 is probably the inhibition site of cyanide and cupric ion in the system.…”
Section: Discussionmentioning
confidence: 63%
“…We found that the inhibition profile of the nitrite reductase activity of the purified cytochrome c552 with several inhibitors coincided with that of the cellular formate/ nitrite reductase [33]. Cytochrome c552 is probably the inhibition site of cyanide and cupric ion in the system.…”
Section: Discussionmentioning
confidence: 63%
“…When nitrate concentration dropped below our limit of detection (0.5 mM) at 8.5 h, the current remained at ~ −0.5 mA, most likely due to the commencement of nitrite reduction. E. coli is known to preferentially reduce nitrate with the stoichiometry 1MKH 2 + 1NO 3 − → 1MK + 1NO 2 − , followed by a switch to nitrite reduction (Lin and Iuchi, 1991), with the stoichiometry 3MKH 2 + 1NO 2 − → 3MK + 1NH 4 (Abou-Jaoude et al, 1979). …”
Section: Resultsmentioning
confidence: 99%
“…Nitrite ammonification is widespread in γ‐proteobacteria [147]. However, the corresponding enzymes or the capability of respiratory nitrite ammonification were characterized in only a few cases.…”
Section: Respiratory Nitrite Ammonification In Other Proteobacteriamentioning
confidence: 99%